EITHER‐SEX TURKEY HARVEST IN THE TEXAS PANHANDLE - Richard D. DeArment (Wildlife Society Bulletin)
Abstract Either‐sex harvests of Rio Grande turkeys (Meleagris gallopavo intermedia) were studied from 1969 through 1972 under the Panhandle Game Management Survey in Hemphill and Wheeler Counties. A total of 1,225 turkeys, 9.7 percent of the population, was harvested.